Pengaruh Foot Massage terhadap Derajat Edema pada Ibu Hamil TM III di Wilayah Kerja Puskesmas Cijagang Kabupaten Cianjur - Yeti Hernawati; Dewi Syanti Pebriyantina; Amida S Sarbib (Jurnal Sehat Masada, 2024)
Oedema occurs in nearly 80% of all pregnancies and can cause discomfort during pregnancy, including pain, heaviness, night cramps, paresthesia, dyspnea, skin thickening, and pigmentation. One of the non-pharmacological interventions to reduce Oedema is foot massage which is an intervention to eliminate or to minimize lower extremity Oedema during pregnancy. The purpose of this study was to analyze the relationship between foot massage and the degree of Oedema in third trimester pregnant women. This research was conducted from February 2023 to March 2023 in the Working Area of the Cijagang Community Health Center, Cianjur Regency. The results of the study obtained data that of the 30 respondents, most of the respondents experienced degree of Oedema 2 in 20 people (66.7%), Degree of Oedema 3 in 10 people (33.3%). The average degree of Oedema before foot massage was given was 4.67 with SD 0.795 and SE 0.145. The average degree of Oedema after being given foot massage was 2.40 with SD 0,279 and SE 0.050. The average difference in the degree of Oedema before (pre-test) and after (post-test) given foot massage was 2.27. The statistical test results obtained a p value = 0.0001 (p <0.05) so it can be concluded that there is a significant relationship between foot massage and the degree of Oedema. It is suggested to health workers, especially midwives, to provide health education and foot massage care as an effort to reduce physiological Oedema in pregnancy.